2019
DOI: 10.3390/su11123440
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Relationship between Sustainable Organisational Practices and Organisational Effectiveness: The Mediating role of Organisational Identification and Organisation-Based Self-Esteem

Abstract: This study ascertains the predictive relationship that sustainable organisational practices have with organisational effectiveness and the mediating role of organisational identification and organisation-based self-esteem in this relationship. One-hundred and forty-five participants (62 males and 83 females) were sampled from 31 privately-owned organisations in Delta State, Nigeria. Regression analysis revealed that sustainable organisational practices positively and significantly predict organisational effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Previous studies have shown that OBSE has many positive consequences for organization such as personal performance (Hahn and Mathews, 2018), sharing new knowledge with others, sharing specific skills and suggesting original ideas at work (Hahn and Mathews, 2018), increasing employees' voice behaviors (Chen et al, 2016), work engagement, organizational commitment and the spirit at work (Nwanzu and Babalola, 2019) and enhancing well-being and reducing stress (Costantini et al, 2019). On the other hand, many factors can lead to OBSE such as social support (Chen et al, 2016), employee participation programs, organizational structure, enriched work and adequate resources and management credibility (Nwanzu and Babalola, 2019).…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…Previous studies have shown that OBSE has many positive consequences for organization such as personal performance (Hahn and Mathews, 2018), sharing new knowledge with others, sharing specific skills and suggesting original ideas at work (Hahn and Mathews, 2018), increasing employees' voice behaviors (Chen et al, 2016), work engagement, organizational commitment and the spirit at work (Nwanzu and Babalola, 2019) and enhancing well-being and reducing stress (Costantini et al, 2019). On the other hand, many factors can lead to OBSE such as social support (Chen et al, 2016), employee participation programs, organizational structure, enriched work and adequate resources and management credibility (Nwanzu and Babalola, 2019).…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…In deciding within the company, the manager can act on behalf of his interests or the interests of stakeholders. Sometimes, there are mistakes when managers make decisions that are related to the decisions that have been made that will provide benefits or vice versa, which affects their reputation as managers [28], [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hasil analis data menunjukan bahwa Organizational Based Self-esteem memilki pengaruh yang positif dan signifikan serta mampu memediasi Pengaruh Spiritual Leadership terhadap Kinerja karyawan PT.Asuransi Sun Life Syariah team Al Fateeh Semarang, hal ini dapat di interpretasikan bahwa, Pimpinan di PT. Asuransi Sun Life Syariah Financial Branch Al-Fateeh Semarang dengan gaya kepemimpinan yang menekankan pada konsep dan nilai-nilai spiritual, dalam sikap dan perilakunya mampu memotivasi bawahannya, meningkatkan Self-Esteem karyawan, dapat dilihat dari sikapnya yang aktif berusaha dalam menemukan materi yang dibutukan untuk mengatasi masalah pekerjaannya dan menggunakan kemampuan serta keahlian mereka secara penuh sehingga hasil kinerjanya lebih makasimal.Hasil penelitian ini didukung oleh (Nwanzu & Babalola, 2019) yang menyatakan bahwa Organizational Based Self-esteem mampu memediasi dan memiliki pengaruh positif pada persepsi dan kemampuan dalam memaksimalkan kemampuan dan gaya kepemimpinan dalam rangka mencapai tujuan organisasi.…”
Section: Pembahasanunclassified